The rise of the states : evolution of American state government - Teaford, Jon C. (Johns Hopkins University studies in historical and political science, 2002)
In The Rise of the States, noted urban historian Jon C. Teaford explores the development of state government in the United States from the end of the nineteenth century to the so-called renaissance of states at the end of the twentieth. Arguing that state governments were not lethargic backwaters that suddenly stirred to life in the 1980s, Teaford shows instead how state governments were continually adapting and expanding throughout the past century. While previous historical scholarship focused on the states, if at all, as retrograde relics of simpler times, Teaford describes how states actively assumed new responsibilities, developed new sources of revenue, and created new institutions. Teaford examines the evolution of the structure, function, and finances of state government during the Progressive Era, the 1920s, the Great Depression, the post--World War II years, and the post--reapportionment era beginning in the late 1960s. State governments, he explains, played an active role not only in the creation, governance, and management of the political units that made up the state but also in dealing with the growth of business, industries, and education. Not all states chose the same solutions to common problems. For Teaford, the diversity of responses points to the growing vitality and maturity of state governments as the twentieth century unfolded.